Unraveling the Nexus between Emotional Intelligence and Cognitive Load Management in Biology Content - Sitiawati Mulyanah; Romy Faisal Mustofa; Mufti Ali (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
21st-century education highlights the importance of understanding cognitive load and emotional intelligence in the context of teaching and learning. The goal in this study to determine the correlation between emotional intelligence and cognitive load of students in biology subjects in Class XI MIPA SMAN 4 Tasikmalaya. The responden is XI MIPA SMAN 4 Tasikmalaya, consisting of 5 classes with a total of 190 students. The research sample was taken using total sampling, where the entire population becomes the sample. The research instrument uses a 44 statement emotional intelligence questionnaire and a 20 statement cognitive load questionnaire. The data analysis technique used is simple correlation testing, namely bivariate.The results of the study show a very strong correlation between emotional intelligence and cognitive load, with a correlation coefficient (R) of 0.972. The emotional intelligence variable contributes 94.4% to the cognitive load, as indicated by the coefficient of determination (R2) of 0.944. The conclusion of this research is that there is a significant correlation between emotional intelligence and cognitive load of students in biology subjects in Class XI SMA Negeri 4 Tasikmalaya.